Access to eye care and support services among adults from minority ethnic communities living with visual impairment in the United Kingdom - Heinze, Nikki; Jones, Lee (Frontiers in Public Health, 2024)
Visual impairment (V.I.) has been associated with a negative impact on a wide range of life domains including activities of daily living, sports and leisure activities, social activities quality-of-life and mental health. There are various eye health and support services available to those living with V.I. in the UK. However, there is some evidence of inequalities relating to ethnicity and eye service use in the UK: adults from minority ethnic communities (MEC) may delay seeking a diagnosis or treatment, be underrepresented among services, which can provide vital support such as early intervention services, and the V.I. register, which can provide financial and functional support. However, much of the evidence requires confirmation or updating and/or relates to a BAME supergroup. This secondary analysis provides preliminary insights into the use of eye health and a range of support services among a sample of MEC, including Asian and black, adults. Although there were few statistically significant differences, the findings provide practical insights into habits and patterns relating to service and mobility aid use among the different groups, highlighting, for instance, that there is scope to increase uptake of support provided by V.I. charities and through the V.I. register among MEC participants.